Tangerang High School Students' Behavior in Protecting Female Reproductive Organs (case study) - Cahyanih, Nadiah; Rayhana, Rayhana (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Background: Knowledge of maintaining reproductive organs is very important for adolescents, because during adolescence there are developments and changes both physically and emotionally. According to statistical data in Indonesia, there are 63 million young women who behave in poor health out of 69.4 million young women in Indonesia. And one of the reasons is the lack of maintaining the health of the reproductive organs. In order to achieve reproductive health, it is necessary to maintain reproductive health. It is based on knowledge, attitudes, and behavior.Objective: The purpose of this study was to determine the relationship between knowledge and attitudes towards the behavior of 10th grade student Tangerang students in maintaining the female reproductive organs.Research Methodology: The type of research used is descriptive analytic. The design used in this study was cross sectional and used a simple random sampling technique with the Slovin formula to determine the total number of respondents 149. Data collection was carried out using a questionnaire distributed online to 10th grade student Tangerang students to protect their reproductive organs.Results: From a total of 149 respondents, the analysis showed that 10th grade student Tangerang students had good knowledge with good behavior as many as 93 students (78.8%).Conclusion: The results of the Chi-Square test showed that there was a relationship between knowledge and behavior towards maintaining reproductive organs in 10th grade student Tangerang students (p-value 0.007 <0.05)Keywords: Maintaining Reproductive Organs, Level of Knowledge, Attitude, Behavior, Relationship between Knowledge and Behavior, Relationship between Attitude and Behavior